THE IMPACT OF LAKE SIPIN TOURISM DEVELOPMENT ON THE COMMUNITY ECONOMY IN PERSPECTIVE ISLAMIC ECONOMICS - Lidya Anggreni (IAIN Lhokseumawe, 2022)
The existence of natural wealth in the form of lakes on the outskirts of urban areash which is then used by local residents to become tourism object has driven economic activity. The purpose of this study is to see how far the impact of the existence of lake sipin tourism in driving the economy from an Islamic perspective. This study uses a qualitative approach with descrifptive methods, namely conducting observations, documentation and interviews an then processed by triangulation techniques. There are 15 informants consisting of the head of the RT, youth groups and traders around the tourist attraction, to determine the criteria for informants, the researchers classify: being around the object of research, feeling a direct effect/impact on the existence of the object under study, and being able to argue when the researcher expresses several questions or statements. Conclusions from the research results is the development of lake sipin tourism is able ato open job opportunities and increase people’s income; the local community plays an important role in the development of lake sipin tourism as the key to success to improve better performance and the results become more optimal; lake sipin tourism has implemented community economic empowerment according to the view of Islamic economics where in Islamic economics it is explained that the community is required to have an active role and participation and the community is included in all programs designedto answer their needs.